Changes in physicochemical and functional properties of whey protein concentrate upon succinylation. (17th October 2016) - Shilpashree, Bosayya Govindaraju; Arora, Sumit; Sharma, Vivek; Chawla, Prince; Vakkalagadda, Ravikumar
Abstract : The highest degree of succinylation was achieved at the level of 6 moles of succinic anhydride/mole of lysine in whey protein concentrate (WPC). Structural modification of protein or the presence of a high negative charge on the surface of protein upon succinylation exposed buried hydrophobic sites. The solubility of succinylated protein derivatives increased at alkaline pH but decreased at acidic pH values as compared to native WPC. The physicochemical properties of succinylated protein derivatives, such as water– and oil– binding capacity, viscosity and emulsion properties increased significantly ( P < 0.05) compared to native WPC, whereas, foaming stability reduced significantly ( P < 0.05) and there was no change in the foaming capacity.